Macroeconomic Determinants of Stock Returns in the Indonesian Food and Beverage Industry - Siagian, Fahri Gunawan; Sihombing, Pardomuan (Research of Economics and Business, 2025)
The objective of this study is to examine the influence of macroeconomic variables specifically exchange rates, interest rates, and inflation on stock returns, both directly and indirectly through beta, within the food and beverage sector. Additionally, it explores the impact of the COVID-19 pandemic. This research adopts a quantitative approach, targeting companies listed on the Indonesia Stock Exchange within the food and beverage industry. Secondary data, sourced through library research, underpins the study, which employs panel data analysis as a primary method. The findings indicate that inflation does not negatively affect stock returns, similar to interest rates and exchange rates, which also show no adverse impact. Furthermore, the COVID-19 pandemic was found to have no positive influence on stock returns in this sector. Regarding systematic risk, beta appears to diminish the effect of inflation, interest rates, and exchange rates on stock returns, while it does not amplify the impact of the COVID-19 pandemic. These results carry significant implications for managers and investors, suggesting that external macroeconomic conditions and beta are not the key determinants of stock returns.